2016
DOI: 10.1089/jwh.2015.5490
|View full text |Cite
|
Sign up to set email alerts
|

Similar But Different: A Comparison of Adnexal Torsion in Pediatric, Adolescent, and Pregnant and Reproductive-Age Women

Abstract: The presentation of adnexal torsion is similar in pediatric and reproductive-age and pregnant women, although the underlying adnexal pathology may be different. Functional ovarian cysts cause the majority of torsion cases in pregnant women. Recurrence of torsion may occur in any age group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 14 publications
1
24
0
Order By: Relevance
“…The most common histological diagnosis has varied among studies and includes teratoma, cystadenoma, and ovarian cyst . In our cohort, the most common diagnosis was teratoma, followed by normal ovary, which supports the idea that ovarian torsion is not only associated with pathological changes but may also occur in the normal ovary . The histological diagnosis varied among the age groups.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The most common histological diagnosis has varied among studies and includes teratoma, cystadenoma, and ovarian cyst . In our cohort, the most common diagnosis was teratoma, followed by normal ovary, which supports the idea that ovarian torsion is not only associated with pathological changes but may also occur in the normal ovary . The histological diagnosis varied among the age groups.…”
Section: Discussionsupporting
confidence: 83%
“…Adnexal torsion can occur at all ages, but the peak prevalence is in women of reproductive age . The most common overall histologic diagnosis varied in different studies . Furthermore, the spectrum of histologic diagnosis of adnexal torsion at different ages has not been thoroughly investigated.…”
mentioning
confidence: 99%
“…8 Melcer et al, found in their study to have right sided torsion in 62.5% while only 36.5% of cases had pathology on left side and remaining 1% were found to have bilateral involvement. 9 In this study, 60% adnexal torsion was in right side in adolescents and postmenopausal group and 50% in reproductive age group. Bilateral torsion was seen in 1 patient in reproductive group and postmenopausal group.…”
Section: Discussionmentioning
confidence: 47%
“…in their study reported that the presence of a multicystic ovary caused by ovulation induction treatment was found in women of reproductive age (20 years to menopause, in 5.5%) and in pregnancy (in 35.5%). [ 3 ] Spitzer et al . also reported that assisted reproductive technology (ART) and ovarian stimulation with ovarian hyperstimulation syndrome (OHSS) increases ovarian torsion in pregnant women.…”
Section: Discussionmentioning
confidence: 99%